Analyses of dual credit in rural eastern Colorado - Gertge, Phyllis A., author; Morgan, George A., advisor (Colorado State University. Libraries, 2004)
Dual credit programs (also called concurrent enrollment) are designed for high school students who enroll and earn credits towards their high school diploma while simultaneously earning college credits in the same course. It is a strategy used by educational institutions to attempt to eliminate barriers between educational levels and provide a seamless education. The purpose of this study was to analyze the available data on dual credit programs at 29 mostly rural high schools served through five college centers of one community college over a time span of nine years. This is the first study completed in Colorado examining the PSEO (Post Secondary Enrollment Options) Act that allows dual credit programs funded by the state. It investigates the variables associated with student access, selection and participation in dual credit courses. The results of the study suggest that the purpose of the legislation is being met. Dual credit enrollment increased from 17% of eligible students in 1995 to about 30% since 2000. Nearly all of the selected high schools provide some dual credit courses to eligible high school students. The data also indicated that there is a strong relationship between schools linked by interactive learning networks and the rate of participation. However, school size, distance from campus, percentage of minorities, and percentage of students on free and reduced lunch were not significantly related to the percentage of students enrolled in dual credit. Since 2001 students were required to have minimum scores on the "Accuplacer" college placement exam in order to enroll in dual credit class; however, there has been little change in enrollment rates. The low scores demonstrated in entry level assessments by students who applied to take dual credit should be noted. The results also demonstrated the impact of the legislation which has allowed 25% of all eligible students to participate in dual credit opportunities over the nine years.
Keywords: community colleges; curricula; teaching; secondary education; curriculum development; community college education